Properties of Eucalyptus benthamii wood for energy production - Silva, Dimas Agostinho (2015)
The objective of this study was to evaluate the energy potential of Eucalyptus benthamii Maiden et Cambage wood. The samples were collected in the municipality of Cerro Negro, Santa Catarina State, Brazil. Samples were collected from 5 trees at 0%, 25%, 50%, 75% and 100% of commercial height. It was determined basic density, high calorific value, elemental composition, immediate chemical analysis, lower calorific value, energy density, carbon storage and energy production. The physical and chemical variables studied and energy potential of wood did not present differences along the stem.